Pengaruh Kepercayaan Diri Terhadap Komunikasi Interpersonal Pada Remaja Akhir Program Studi Komunikasi Dan Penyiaran Islam di Institut Agama Islam Al-Zaytun Indonesia - Zarah Fazirah; Muhammad N. Abdurrazaq; Wiena Safitri (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This research examines the influence of self-confidence on interpersonal communication directed at two groups, namely people who are known and people who are not known in late adolescence. The main problem behind this research is that when researchers observe the surrounding environment, they see a lack of self-confidence in late adolescents in interpersonal communication. This research method uses a quantitative approach with questionnaire techniques. The sample in this study was 61 students for known people and 24 students for unknown people. The results of the first research from hypothesis testing using the Pearson Correlation test technique showed a Sig. (2-tailed) is 0.666 > 0.05, it can be concluded that Ha is rejected and Ho is accepted, so there is no influence of Self-Confidence on Interpersonal Communication in Final Adolescents of the KPI Study Program at IAI AL-AZIS for known people. The second study used the Spearman Rank correlation test technique showing a Sig value. (2-tailed), namely 0.002 < 0.05, it can be concluded that Ha is accepted and Ho is rejected, so there is an influence of Self-Confidence on Interpersonal Communication in Final Adolescents of the KPI Study Program at IAI AL-AZIS Indonesia for unknown people.